War story : Vietnam war poems - McCarthy, Gerald, 1947- (Trumansburg, N.Y. : Crossing Press, 1977)
Poems depicting life on the battlefield, the return to the United States, and adjustment to civilian life.
Keywords: Vietnamese Conflict, 1961-1975 -- Poetry; Vietnamese Conflict, 1961-1975 -- Poetry; American poetry; 1961-1975; Poetry